Performance and efficiency in Colombia's power distribution system: Effects of the 1994 reform (2006)
We assess evolution in performance, efficiency and productivity of Colombia's power distribution utilities before and after the 1994 regulatory reform that introduced electricity market activities for the power sector in 12 distribution companies from 1985 to 2001. Performance is evaluated contrasting changes in mean and median by Wilcoxon Rank Sum and Pearson tests on financial and other performance indicators. Technical efficiency is measured by means of Data Envelopment Analysis (DEA). The nature of the dataset allows the estimation of Malmquist productivity index and its evolution in time. Results show a recovery after the reform in the main performance indicators of profitability, partial input productivity, and output. Plant efficiency and productivity increased after the reform, mainly in the largest utilities used as benchmarks in the DEA efficiency scores measures. Meanwhile, the less efficient power distribution companies did not improved after the reform and were not able to undertake plant restructuring to catch-up in plant efficiency with respect to the Pareto efficient input allocations. Econometric results on DEA efficiency scores suggest a positive effect of policy reform. © 2005 Elsevier B.V. All rights reserved.